6000 Awesome Facts - Kelly;Miles (Essex Miles Kelly Publishing Ltd, 2018)
ntastic reference resource covers a wide spectrum of subjects including Mammals, Human Body and Prehistoric Life. Subject panels with bulleted facts are accompanied by detailed illustrations, diagrams and photographs, while Did You Know panels provide scattered chunks of extraordinary information.